ReMindCare, an app for daily clinical practice in patients with first episode psychosis: A pragmatic real‐world study protocol. Issue 1 (6th April 2020) - Bonet, Lucia; Torous, John; Arce, David; Blanquer, Ignacio; Sanjuán, Julio
Abstract: Aim: Despite the potential benefits of e‐health interventions for patients with psychosis, the integration of these applications into the clinical workflow and analysis of their long‐term effects still face significant challenges. To address these issues, we developed the ReMindCare app. This app aims to improve the treatment quality for patients with psychosis. We chose to study the app in real world and pragmatic manner to ensure results will be generalizable. Methods: This is a naturalistic empirical study of patients in a first episode of psychosis programme. The app was purpose‐designed based on two previous studies, and it offers the following assessments: (a) three daily questions regarding anxiety, sadness and irritability; and (b) 18 weekly questions about medication adherence, medication side effects, medication attitudes and prodromal symptoms. The app offers preset alerts, reminders and the ability for patients to reach out to their clinicians. Data captured by the app are linked to the electronic medical record of the patient. Patients will use the app as part of their ongoing care for a maximum period of 5 years, and assessments will occur at baseline and at the end of the first, second and fifth years of app use. Results: Recruitment started in October 2018 and is still ongoing. Conclusions: The ReMindCare app represents early real‐world use of digital mental health tools that offer direct integration into clinical care. High retention and compliance rates are expected, and this will in turn lead to improved quality of assessments and communication between patients and clinicians.